2022
DOI: 10.2147/iprp.s346395
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Pattern of Dermatological Compounding in Ethiopia: The Case of ALERT Hospital

Abstract: Background: Skin diseases are among the major contributors of disease burden in Ethiopia affecting individuals of all age. Extemporaneous compounding of topical medications serves as a necessary option to treat skin diseases when manufactured medications could not meet specific patient needs. Different classes of drugs are commonly used for the treatment of dermatologic diseases. Failure to periodically assess the prescribing pattern and patient needs may lead to inappropriate planning and implementation that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…It indicated that the general major illnesses as faced by both the groups were almost same. Several studies [e.g., ( 64 , 67 , 68 , 78 )] also found similar results, which confirmed the findings of the present study. Stressful occupation causes some major diseases, which frequently attacked the respondents, were also investigated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It indicated that the general major illnesses as faced by both the groups were almost same. Several studies [e.g., ( 64 , 67 , 68 , 78 )] also found similar results, which confirmed the findings of the present study. Stressful occupation causes some major diseases, which frequently attacked the respondents, were also investigated.…”
Section: Discussionsupporting
confidence: 93%
“…Considered a public health problem due to its impact on workers' health, work-related stress can be seen as an illness that has emerged in modern society. Different reports indicate that workplace stress affects workers' health risk i.e., physical health, mental health, and behavior ( 33 , 66 , 67 ). Stress contributes to decreased organizational performance, decreased employee overall performance, high error rate and poor quality of work, high staff turnover, absenteeism and health risk.…”
Section: Literature Reviewmentioning
confidence: 99%